Analisis Pelaksanaan Program Indonesia Sehat Dengan Pendekatan Keluarga di Tingkat Puskesmas Kota Tidore Kepulauan - Dewi Indra Purwanti (Peneliti.net, 2021)
The objective of this study was to determine the implementation of the Indonesia Healthy Program with a Family Approach (PIS-PK) in Local goverment Clinic at Tidore Islands. This research is qualitative research, its take place in 2 Local goverment clinic namely, Puskesmas Soasio and Puskemas Tomalou. Those two Local goverment clinic are location in Tidore City, North Maluku Province, carried out from April to August 2019. The informants of this study were the PIS PK coordinators at the public health center level. the head of the public health center, the coordinator of PIS-PK of the Tidore City Health Office and 63 heads of families from each working area of ​​the Local goverment public. The results of the study concluded that in general, the implementation of PIS-PK at the level of Local goverment clinic in the City of Tidore Islands has been implementedl as well as the program implementation guidelines. In the event that the socialization process has been carried out according to the objectives and stages in the program activity plan, it is necessary to increase cross-sectoral synergy and elements of interest. Availability of Human Resources in public health centers has been in accordance with the needs of program implementation, but it is necessary to evaluate performance and increase competence to improve services. The activity budget is available from the Health Operational Assistance (BOK) as well as the National Health Insurance (JKN) capitation and routine funds for public health centers, but a budget allocation for additional medical devices is required for follow-up interventions for community conditions and service needs at public health centers. Family Health Profile (PROKESGA) data is available, but needs continuous updating. The Family Information Package (PINKESGA) as a family education instrument is also available. PIS-PK activities running well because of a roadmap with an activity plan, which is agreed with the relevant elements as a reference for the implementation of PIS-PK activities.